Hypofractionated Palliative Radiotherapy for Relapsed and Refractory High-Risk Neuroblastoma - Ellery Koelker-Wolfe; Karen J. Marcus; Steven G. DuBois; Paul J. Catalano; Suzanne Shusterman; Myrsini Ioakeim-Ioannidou; Hesham Elhalawani; Torunn I. Yock; Shannon M. MacDonald; Daphne A. Haas-Kogan; Kevin X. Liu (Current Oncology)
Introduction: While palliative radiotherapy (RT) is frequently used in the management of relapsed/refractory high-risk neuroblastoma (HR-NBL); outcomes after palliative hypofractionated RT (hypo-RT) remain poorly characterized. Methods: We conducted a multi-institutional retrospective study of 38 patients who were diagnosed with HR-NBL between 1997 and 2021 and received palliative RT. Conventional RT (conv-RT) and hypo-RT were defined as palliative treatment courses using dose ≤2 or >2 Gy per fraction, respectively. The primary outcome was cumulative incidence of in-field progression using Gray’s test. Univariate analyses were performed using the Cox proportional hazards model. Results: When analyzing by first course of palliative RT, 16 patients received conventionally fractionated RT (43%) and 21 received hypo-RT (57%). Clinical characteristics were similar between the two groups. With a median follow-up of 10.3 months (range: 0.3–104.0), the cumulative incidence of in-field progression was not statistically significantly different between hypo-RT and conv-RT (30% vs. 20% at 10 months; p = 0.80). Clinical response, defined as symptomatic improvement or decrease in the size of the lesion, was not statistically different between the two groups (92% conv-RT vs. 90% hypo-RT; p = 1.00). No grade ≥4 toxicities were observed. On univariate analysis, hypo-RT (HR 1.50; 95% CI 0.47–4.76; p = 0.493) was not statistically significantly associated with time to in-field progression, but MYCN amplification was associated with significantly longer time to in-field progression (HR: 0.20; 95% CI: 0.05–0.77; p = 0.020). Conclusions: We found no statistically significant difference in cumulative incidence of in-field progression and clinical outcomes between the conv-RT and hypo-RT groups. Palliative hypo-RT can be considered for relapsed/refractory HR-NBL, especially when shorter treatments may offer improved quality of life.